A Perspective on COVID-19 Management - Pavelić, Krešimir (J Clin Med, 2021)
A novel coronavirus—Severe Acute Respiratory Syndrome-Coronavirus 2 (SARS-CoV-2)—outbreak correlated with the global coronavirus disease 2019 (COVID-19) pandemic was declared by the WHO in March 2020, resulting in numerous counted cases attributed to SARS-CoV-2 worldwide. Herein, we discuss current knowledge on the available therapy options for patients diagnosed with COVID-19. Based on available scientific data, we present an overview of solutions in COVID-19 management by use of drugs, vaccines and antibodies. Many questions with non-conclusive answers on the measures for the management of the COVID-19 pandemic and its impact on health still exist—i.e., the actual infection percentage of the population, updated precise mortality data, variability in response to infection by the population, the nature of immunity and its duration, vaccine development issues, a fear that science might end up with excessive promises in response to COVID-19—and were raised among scientists. Indeed, science may or may not deliver results in real time. In the presented paper we discuss some consequences of disease, its detection and serological tests, some solutions to disease prevention and management, pitfalls and obstacles, including vaccination. The presented ideas and data herein are meant to contribute to the ongoing debate on COVID-19 without pre-selection of available information.